Modeling of the Lattice Dynamics in Strontium Titanate Films of Various Thicknesses: Raman Scattering Studies - Krasnenko, Veera; Platonenko, Alexander; Liivand, Aleksandr; Rusevich, Leonid L.; Mastrikov, Yuri A.; Zvejnieks, Guntars; Sokolov, Maksim; Kotomin, Eugene A. (MDPI, 2023)
While the bulk strontium titanate (STO) crystal characteristics are relatively well known, ultrathin perovskites’ nanostructure, chemical composition, and crystallinity are quite complex and challenging to understand in detail. In our study, the DFT methods were used for modelling the Raman spectra of the STO bulk (space group I4/mcm) and 5–21-layer thin films (layer group p4/mbm) in tetragonal phase with different thicknesses ranging from ~0.8 to 3.9 nm. Our calculations revealed features in the Raman spectra of the films that were absent in the bulk spectra. Out of the seven Raman-active modes associated with bulk STO, the frequencies of five modes (2Eg, A1g, B2g, and B1g) decreased as the film thickness increased, while the low-frequency B2g and higher-frequency Eg modes frequencies increased. The modes in the films exhibited vibrations with different amplitudes in the central or surface parts of the films compared to the bulk, resulting in frequency shifts. Some peaks related to bulk vibrations were too weak (compared to the new modes related to films) to distinguish in the Raman spectra. However, as the film thickness increased, the Raman modes approached the frequencies of the bulk, and their intensities became higher, making them more noticeable in the Raman spectrum. Our results could help to explain inconsistencies in the experimental data for thin STO films, providing insights into the behavior of Raman modes and their relationship with film thickness. © 2023 by the authors. --//-- Krasnenko V., Platonenko A., Liivand A., Rusevich L.L., Mastrikov Y.A., Zvejnieks G., Sokolov M., Kotomin E.A.; Modeling of the Lattice Dynamics in Strontium Titanate Films of Various Thicknesses: Raman Scattering Studies; (2023) Materials, 16 (18), art. no. 6207; DOI: 10.3390/ma16186207; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85172725318&doi=10.3390%2fma16186207&partnerID=40&md5=32f343f9cb8da145c6647566cb534c32. Published under the CC BY 4.0 license.
This paper is partly based upon COST (European Cooperation in Science and Technology) Action 18234 (E.A.K., M.S., and V.K.) and financially supported by FLAG-ERA JTC project To2Dox (Y.A.M). The Institute of Solid State Physics, University of Latvia (Latvia), as the Centre of Excellence has received funding from the European Union’s Horizon 2020 Frame-work Programme H2020-WIDESPREAD-01-2016-2017-Teaming Phase2 under grant agreement No. 739508, project CAMART2. The computer resources were provided by the High-Performance Computing Centre Stuttgart (HLRS project DEFTD 12939). In addition, the research of V.K. and A.P. was partly supported by the RADON project (GA 872494) within the H2020-MSCA-RISE-2019 call.
Keywords: Research Subject Categories::NATURAL SCIENCES; dependence on thickness; DFT; Raman calculations; STO; ultrathin films